(untitled) (Confluenţe Bibliologice, 2021)
The author reports information from O.N.T magazine. nr. 8-9, August-September 1939, which has as main subject the Romanian Mountains and it is beautifully illustrated with 32 images. He also selects some passages that seem to be the most interesting. The tourist beauty of the Mountains are indescribable. He makes an interesting presentation of Romania’s exhibitions in Paris and New York. For climbers, there is a material with new routes in the Abruptul Pietrei Craiului. There are no less than 10 alpine routes, with many details specific to mountaineering.